2020
DOI: 10.1016/j.cjph.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamics (MHD) axisymmetric flow and heat transfer of a hybrid nanofluid past a radially permeable stretching/shrinking sheet with Joule heating

Abstract: The main interest of the present work is to fundamentally investigate the flow characteristics and heat transfer of a hybrid Cu-Al2O3/water nanofluid due to a radially stretching/shrinking surface with the mutual effects of MHD, suction and Joule heating. The surface is permeable to physically allow the wall mass fluid suction. Tiwari and Das model of nanofluid is used with the new thermophysical properties of hybrid nanofluid to represent the problem. A similarity transformation is adopted to convert the gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(89 citation statements)
references
References 61 publications
0
83
0
Order By: Relevance
“…There have been considered the incompressible 2D, MHD, and steady boundary layer flow of hybrid nanofluid with the effects of Joule heating, velocity, and thermal slip conditions over the exponentially shrinking surface (see Figure 1) without the viscous dissipation effect. By considering all assumptions, the governing mass, momentum, and energy conservations can be expressed as [35,37]:…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been considered the incompressible 2D, MHD, and steady boundary layer flow of hybrid nanofluid with the effects of Joule heating, velocity, and thermal slip conditions over the exponentially shrinking surface (see Figure 1) without the viscous dissipation effect. By considering all assumptions, the governing mass, momentum, and energy conservations can be expressed as [35,37]:…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…In addition, stability analysis on the solutions was done and demonstrated that only the first solution is stable. Meanwhile, the axisymmetric flow of electrically conducting hybrid nanofluid was inspected by Khashi'ie et al [35], in whose work the occurrence of dual solutions is noticed within certain ranges of physical parameters. The stability analysis also specified that only the first solution is stable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this model has been widely employed by many researchers, such as Hayat et al [21], Saba et al [22], Acharya et al [23], Afridi et al [24], Shafiq et al [25,26], and Manh et al [27]. Furthermore, Khashi'ie et al [28] found dual solutions of magnetohydrodynamic (MHD) flow of a hybrid nanofluid in the presence of Joule heating and noticed that higher values of Eckert number do not affect boundary layer separation. Lund et al [29] studied hybrid nanofluids by considering copper and alumina as solid particles with water as a base fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Set of differential equations comprises of Navier–Stokes equations and Maxwell’s equations describes the complete phenomenon of MHD. Kashi’ie et al 28 numerically investigated the flow properties for the dynamics of fluidic system and phenomena of heat transfer for a MHD flow of hybrid nanofluid (Al 2 O 3 /H 2 O) due to stretching sheet while considering the joule heat effects. Osho et al 29 discovered the flow characteristics of hybrid nanofluid (Al 2 O 3 -Zn/H 2 O) and noticed the significant effect of concentration of nanoparticles over the viscosity and specific heat of the flow.…”
Section: Introductionmentioning
confidence: 99%